2007
DOI: 10.1074/jbc.m706024200
|View full text |Cite
|
Sign up to set email alerts
|

Fe65 Stimulates Proteolytic Liberation of the β-Amyloid Precursor Protein Intracellular Domain

Abstract: The ␤-amyloid precursor protein (APP)-binding protein Fe65 is involved in APP nuclear signaling and several steps in APP proteolytic processing. In this study, we show that Fe65 stimulates ␥-secretase-mediated liberation of the APP intracellular domain (AICD). The mechanism of Fe65-mediated stimulation of AICD formation appears to be through enhanced production of the carboxyl-terminal fragment substrates of ␥-secretase and direct stimulation of processing by ␥-secretase. The stimulatory capacity of Fe65 is is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…We also showed that coexpression of Fe65 negated the inhibitory effect of NMDA on AICD-Gal4-driven luciferase activity, and this may be explained by the recent finding that overexpression of Fe65 isoforms robustly stimulates AICD levels by increasing both the rate of ␣-CTF (C83) and ␤-CTF (C99) production and the rate of ␥-secretase-mediated cleavage of its immediate substrates (C83 and C99) (Wiley et al, 2007).…”
Section: Nmda Receptor Activity Regulates C83 Ctf Levelsmentioning
confidence: 85%
See 1 more Smart Citation
“…We also showed that coexpression of Fe65 negated the inhibitory effect of NMDA on AICD-Gal4-driven luciferase activity, and this may be explained by the recent finding that overexpression of Fe65 isoforms robustly stimulates AICD levels by increasing both the rate of ␣-CTF (C83) and ␤-CTF (C99) production and the rate of ␥-secretase-mediated cleavage of its immediate substrates (C83 and C99) (Wiley et al, 2007).…”
Section: Nmda Receptor Activity Regulates C83 Ctf Levelsmentioning
confidence: 85%
“…It has previously been reported that the AICD is a highly labile fragment that is stabilized when complexed with Fe65 (Kimberly et al, 2001); however, a more recent study has shown that overexpression of Fe65 stimulates both liberation of AICD from full-length APP and luciferase reporter gene transcription driven by an APP-Gal4VP16 fusion protein (Wiley et al, 2007). We examined whether Fe65 regulates APP695-Gal4-driven luciferase activity in primary cortical neurons and found that neurons cotransfected with plasmids encoding for APP695-Gal4 and Fe65 produced 15-20 times more luciferase activity than neurons transfected with APP695-Gal4 plasmid alone (Fig.…”
Section: Synaptic Nmda Receptor Activity Increases ␣-Ctf (C83) Levelsmentioning
confidence: 99%
“…Multiple AβPP-derived peptides are produced with varying length thereby affecting the reactivity with antibodies employed for immunoassay, and likely, varying the extractability from lysed cells. Consequently, we have employed a procedure that monitors γ-secretase mediated release of the intracellular domain (AICD) of AβPP, since release of Aβ peptides from AβPP by γ-secretase is accompanied by release of AICD (16,18). The methodology involves expression of AβPP modified by C-terminal fusion to a transcription factor, so that AICD release drives expression of a luciferase reporter gene.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, FE65 and FE65L1 stimulate APP intracellular domain (AICD) generation (Chang et al, 2003;Wiley et al, 2007;Xie et al, 2007). However, the identification of several putative target genes have been controversially discussed (Baek et al, 2002;Bimonte et al, 2004;Müller et al, 2007;Telese et al, 2005;von Rotz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%